HELLP syndrome: a complication or a new autoimmune syndrome? - Paola Triggianese (Rheumatology, 2014)
The HELLP (hemolysis, elevated liver enzymes, low platelets) syndrome is a pregnancy-specific disease characterized by hemolysis with elevated lactate dehydrogenase, elevated liver enzymes, and decreased platelet count. It is considered a severe variant of the hypertensive disorders that occur during pregnancy together with the pre-eclampsia (PE) and the eclampsia giving symptoms in the mother from 20 weeks’ gestation onward. All these conditions are multi-system pregnancy-related diseases associated with an increase in blood pressure and in both the perinatal and the maternal morbidity/mortality. Observational studies suggest that steroid treatment in HELLP syndrome may improve the hematological and biochemical features in the mother and the perinatal outcome. The present review aims to show that the HELLP syndrome may be considered as an autoimmune disorder itself. Biomarkers of the immune system can be a useful tool improving the diagnostic and therapeutic management of women with HELLP by delineating the underlying etiology of this syndrome.